Evaluation of Botanical - Insecticide modules against stem borer, brown planthopper and natural enemies in rice - A D V S L P, Anand Kumar; Kishore M, Nanda; Rao N, Srinivasa; D, Lalitha; T, Srinivas (International Journal of Environment, Agriculture and Biotechnology, 2024)
Field experiment was conducted at Regional Agricultural Research Station, Maruteru, West Godavari (A.P.) during fourrabi seasons of 2019-20to 2022-23 to evaluate botanical-insecticide modules against stem borer and brown planthopper. Significantly superior results were recorded in insecticides alone module, T4 (Chlorantraniliprole 0.4 G @ 1.0 g m-2, Cartap hydrochloride 50% SC @ 2.0 g l-1, Triflumezopyrim 10% SC @ 0.48 ml l-1 applied at 25, 45 and 60 DAT respectively) with 50% ROC, 33% ROC in dead hearts and white ears, respectively in case of stem borer and 94% ROC in brown planthopper population and registered the highest grain yield.Among botanical – insecticide modules, treatment, T2 (Azadirachtin 10000 ppm @ 2.0 ml l-1, Neem oil @ 10.0 ml l-1 and Triflumezopyrim 10% SC @ 0.48 ml l-1 applied at 25, 45 and 60 DAT respectively) is the best against stem borer (26% ROC in dead heart damage & 13% ROC in white ear damage) and brown planthopper (91% ROC in brown planthopper population). Further, T2 is at par with insecticides alone module (T4) in managing stem borer and BPH and recorded the grain yield (6718 kg ha-1) on par with the insecticides alone module (6824 kg ha-1).